The Effect of Compliance Clinical Pathway on the Quality Of Service, Cost of Treatment, Length of Stay at Linggajati Hospital - Roheman; M.F. Arrozi; Sandra Dewi (Jurnal Cinta Nusantara, 2025)
Clinical pathways are essential for achieving good clinical governance in hospitals as they standardize patient care. However, the compliance with the implementation of the inguinal hernia clinical pathway at Linggajati Hospital does not meet the minimum standard of 80%. Specifically, the service quality is below the desired 80%, treatment costs do not align with INA CBGs standards, and the length of stay exceeds the recommended ≤3 days. This study aims to analyze the effect of compliance with the implementation of the inguinal hernia clinical pathway on service quality, treatment costs and length of stay at Linggajati Hospital. This type of research is survey research. The population of this study was the medical records of inguinal hernia patients from January 2023 to June 2024. The sample in this study was 204 respondents taken using the purposive sampling technique. Univariate data analysis uses frequency distribution and the Three Box Method, and multivariate analysis uses multinomial regression and ordinary least squares (OLS) regression. Results: Compliance with the implementation of the inguinal hernia clinical pathway does not have an impact on the quality of service and cost of care but only has an impact on the length of stay at Linggajati Hospital with an R-square value of 0.039 and a P-value of 0.000. Conclusions: The results of this research have implications for providing information to health workers to further optimise clinical pathway compliance and monitor quality control evaluation and hospital care costs.